(untitled) (Journal of history, 2022)
The Kazakh nation has come a long and difficult way in history. Kazakh statehood has taken a multifaceted model in different historical periods. However, a full-fledged modern statehood that meets the national interests and can withstand the challenges of the XXI century has been established in 1991 only after the collapse of the USSR. For many years, the country has been fighting for independence, experiencing the fate of the country, and in a short period of time, the Kazakh nation has regained its sovereign statehood in a time of forgetfulness, and is stepping into the future among the world’s leading nations. In a short period of time, the state has identified the political aspects of its development, made the transition to a market economy, and experienced serious social commotions. The first Kurultay of the Worldwide Kazakhs convened in 1992 discussed the establishment of the World Association of Kazakhs and the election of its charter and governing bodies. At the scientific conference of the Kurultay, the World Association of Kazakhs was established. The first step of our independent country was to invite our compatriots from all over the world to the first kurultai of the worldwide Kazakhs. In Almaty, the capital of the Kazakh people, there was a great gathering of the nation, which brought together Kazakhs from all over the world. Since then, as a result of the work carried out, the number of compatriots who came to the country in 2019 reached 1.5 million people. Kazakhstan has established regular contacts with ethnic Kazakhs abroad. Key words: diaspora, foundation, association, society, Kazakh country.